ChemInform Abstract: Fe2.25W0.75O4/Reduced Graphene Oxide Nanocomposites for Novel Bifunctional Photocatalyst: One‐Pot Synthesis, Magnetically Recyclable and Enhanced Photocatalytic Property. Issue 42 (1st October 2013) - Guo, Jinxue; Jiang, Bin; Zhang, Xiao; Zhou, Xiaoyu; Hou, Wanguo
Abstract The title nanocomposites are hydrothermally prepared from aqueous solutions containing Na2WO4, FeSO4, graphene oxide, NaOH, and sodium dodecyl benzene sulfonate (autoclave, pH 10, 180 °C, 12 h).